Impact of dietary vitamin D on immunoregulation and disease pathology in lupus-prone NZB/W F1 mice - Kraemer, Antoine N.; Schäfer, Anna-Lena; Sprenger, Dalina T. L.; Sehnert, Bettina; Williams, Johanna P.; Luo, Aileen; Riechert, Laura; Al-Kayyal, Qusai; Dumortier, Hélène; Fauny, Jean-Daniel; Winter, Zoltan; Heim, Kathrin; et al. (Frontiers in Immunology, 2022)
Vitamin D (VD) deficiency is a highly prevalent worldwide phenomenon and is extensively discussed as a risk factor for the development of systemic lupus erythematosus (SLE) and other immune-mediated diseases. In addition, it is now appreciated that VD possesses multiple immunomodulatory effects. This study aims to explore the impact of low dietary VD intake on lupus manifestation and pathology in lupus-prone NZB/W F1 mice and to identify the underlying immunological mechanisms modulated by VD. Here, we show that low VD intake accelerates lupus progression, reflected in reduced overall survival, earlier onset of proteinuria, as well higher concentrations of anti-dsDNA autoantibodies. This unfavorable effect gained statistical significance with additional low maternal VD intake during the prenatal period. Among examined immunological effects, we found that low VD intake consistently hampered the adoption of a regulatory phenotype in lymphocytes, significantly reducing both IL-10-expressing and regulatory CD4+ T cells. This goes along with a mildly decreased frequency of IL-10-expressing B cells. We did not observe consistent effects on phenotype and function of innate immune cells, including cytokine production, co-stimulatory molecule expression and phagocytic capacity. Hence, our study reveals that low VD intake promotes lupus pathology, likely via the deviation of adaptive immunity, and suggests that the correction of VD deficiency might not only exert beneficial functions by preventing osteoporosis, but also serve as an important module in prophylaxis and as an add-on in the treatment of lupus and possibly other immune-mediated diseases. Further research is required to determine the most appropriate dosage, as too high VD serum levels may also induce adverse effects, possibly also on lupus pathology.